Serratus Anterior Block as Analgesia in Post-Thoracotomy Patients: Serial Case - Parathon, Nugroho Satya; Basuki, Djudjuk Rahmad (Journal of Anaesthesia and Pain, 2022)
Providing analgesia in postoperative period for those undergone thoracotomy is chalenging, because nessesity to relieve postoperative pain and to prevent pulmonary complication following thoracotomy. Analgesic options for thoracotomy are various with each having benefits and disadvantages. It is mentioned that thoracic epidural is the gold standard for management of thoracotomy pain. Other option include paravertebral block, interpleural block, intrathecal opioid. Serratus anterior plane block (SAPB) is a relatively new compartment block technique for thoracic wall pain first developed in 2013 by Blanco et al. SAPB is a sensory nerve block that provides analgesia to the ipsilateral hemithorax form second thoracic (T2) to T9 dermatomes. SAPB has ben used in several procedure such as breast surgery, thoracoscopy, rib fracture analgesia, and shoulder injury as a good alternative analgesic method after thoracoscopic surgeries.This case series found that SAPB was an effective as post-operative analgesia after thoracotomy with good efficacy. Further investigation is still needed to determine the role of SAPB in the management of a variety of patients with acutely painful conditions and to understand possible side effects that my arise.